2008
DOI: 10.1080/10550490802138814
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Buprenorphine and Bupropion for Opioid‐Dependent Smokers

Abstract: In this double-blind, placebo-controlled trial, bupropion (BUPRO, 300 mg/day) was compared to placebo (PBO) for concurrent treatment of opioid and tobacco addiction in 40 opioid-dependent smokers stabilized on buprenorphine (BUPRE, 24 mg/day). Participants received contingent, monetary reinforcement for abstinence from smoking, illicit opioids, and cocaine. Significant differences in treatment retention were observed (BUPRE+BUPRO, 58%; BUPRE+PBO, 90%). BUPRO treatment was not more effective than placebo for ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 38 publications
(49 reference statements)
3
44
0
Order By: Relevance
“…13,22,52Y55 Results have shown negative results or modest success in smoking cessation rates. Recently, Mooney et al 52 noted that there continues to be a deficiency of evidenced-based smoking cessation treatment options in opioid-dependent individuals.…”
Section: Discussionmentioning
confidence: 98%
“…13,22,52Y55 Results have shown negative results or modest success in smoking cessation rates. Recently, Mooney et al 52 noted that there continues to be a deficiency of evidenced-based smoking cessation treatment options in opioid-dependent individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Tobacco cessation treatments have modest efficacy among patients in MMT (Miller and Sigmon, 2015), but only one trial has tested their effects among patients in buprenorphine treatment (Mooney et al, 2008). Though some studies have described tobacco use characteristics among BMT patients (Chisolm et al, 2013; Pajusco et al, 2012), none to date have described smoking cessation treatment experience in this group.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of MMT smokers, poor medication adherence has been identified as a significant barrier to successfully quitting Mooney et al, 2008;Richter et al, 2001;Stein et al, 2006Stein et al, , 2007.…”
Section: Quit Initiation and Treatment Adherencementioning
confidence: 99%
“…Yet, all of the smoking cessation pharmacotherapies that have been tested in opioiddependent persons have far lower quit rates (Mooney et al, 2008;Okoli et al, 2010;Reid et al, 2008;Shoptaw et al, 2002;Stein et al, 2006) than those reported in trials of nondrug users (Hurt et al, 1994;Mooney et al, 2008;Okoli et al, 2010;Reid et al, 2008;Shoptaw et al, 2002;Stead et al, 2008;Stein et al, 2006). Over the last two decades, there have been four fully powered randomized clinical trials (RCTs) involving smoking cessation interventions specifically with MMT smokers (Haug, Advance Access publication June 20, 2014 nicotine & tobacco research, volume 16, number 11 (november 2014) 1463-1469 early quit days among methadone-maintained smokers Svikis, & Diclemente, 2004;Shoptaw et al, 2002;Stein et al, 2006Stein et al, , 2013Story & Stark, 1991).…”
Section: Introductionmentioning
confidence: 99%